Accurate and precise measurement of uranium content in uranium trioxide by gravimetry: Comparison with isotope dilution mass spectrometry and its uncertainty estimation. (December 2022) - Yamamoto, Masahiko; Horigome, Kazushi; Kuno, Takehiko
Abstract: Gravimetric measurement of U content in UO3 with ignition in air has been investigated. The ignition temperature, ignition time and aliquot sample mass are optimized as 900 °C, 60 min, and 1 g, respectively. The method is validated by isotope dilution mass spectrometry (IDMS) with uncertainty estimation. The obtained result by gravimetry is 0.78287 ± 0.00051 g/g (k = 2) and agreed with IDMS value. It has been found that U in UO3 can be measured accurately and precisely by gravimetry. Graphical abstract: Image 1 Highlights: Gravimetric determination of U in UO3 was investigated. Ignition temperature, ignition time and aliquot sample mass were optimized. Measurement results of U content in UO3 by gravimetry was validated by IDMS. Uncertainty of UO3 gravimetric measurement was estimated.